(untitled) (Revista de Investigaciones Universidad del Quindío, 2023)
The complexity for a political government to be, in turn, a scientific government is debated. First, a reflection is made on the idealization of politicians as government officials. Second, insights into the historical government demand for better administrators are generated and organizational differences between advanced and lagging systems are clarified. Finally, a criticism is made about the role of political parties as social devices that have left aside the quality in the training of the State’s human resources.